Comparison of screening strategies to improve the diagnosis of latent tuberculosis infection in the HIV-positive population: a cohort study. Issue 2 (1st March 2012) - Pollock, Katrina M; Tam, Herman; Grass, Lisa; Bowes, Sharleen; Cooke, Graham S; Pareek, Manish; Montamat-Sicotte, Damien; Kapembwa, Moses; Taylor, Graham P; Lalvani, Ajit
Abstract : Background: HIV is the most important risk factor for progression of latent tuberculosis infection (LTBI) to active tuberculosis (TB). Detection and treatment of LTBI is necessary to reduce the increasing burden of TB in the UK, but a unified LTBI screening approach has not been adopted. Objective: To compare the effectiveness of a TB risk-focused approach to LTBI screening in the HIV-positive population against current UK National Institute for Health and Clinical Excellence (NICE) guidance. Design: Prospective cohort study. Setting: Two urban HIV treatment centres in London, UK. Participants: 114 HIV-infected individuals with defined TB risk factors were enrolled prospectively as part of ongoing studies into HIV and TB co-infection. Outcome measures: The yield and case detection rate of LTBI cases within the research study were compared with those generated by the NICE criteria. Results: 17/114 (14.9%, 95% CI 8.3 to 21.5) had evidence of LTBI. Limiting screening to those meeting NICE criteria for the general population (n=43) would have detected just over half of these, 9/43 (20.9%, 95% CI 8.3 to 33.5) and those meeting criteria for HIV co-infection (n=74) would only have captured 8/74(10.8%, 95% CI 3.6 to 18.1) cases. The case detection rates from the study and NICE approaches were not significantly different. LTBI was associated with the presence of multiple TB risk factors (p=0.002). Conclusion: Adoption of a TB risk-focused screening algorithm that does not use CD4 count stratification could prevent more cases of TB reactivation, without changing the case detection rate. These findings should be used to inform a large-scale study to create unified guidelines.